Strategi Pemasaran Produk Gadai Emas dalam Menarik Minat Nasabah Pada Bank Syariah Indonesia KCP Medan Marelan Raya - Elvina, Ayu; Indra, Ahmad Perdana (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
The purpose of this study was to find out how the marketing strategy of gold pawn products at Bank Syariah Indonesia KCP Medan Marelan Raya. This research is a qualitative research with descriptive method while the data collection technique is by conducting interviews and observation. to make Sharia Gold Pawn product at KCP Medan Marelan Raya, a strategy is needed so that the sales objectives of the product can be successful and meet the company’s targets. Then do a SWOT analysis first so that the strategy used is right on target. This research uses SWOT analysis with marketing mix theory. The results of this study indicate that the Sharia Gold Pawn at KCP Medan Marelan Raya has developed quite well, which means that customers are interested or interested in the Sharia Gold Pawn with evidence of ank increase in the number of gold pawn customers from 2021-2022. Therefore, the marketing strategy plays a role very important in increasing the number of customers on the Sharia Gold Pawn at Bank Syariah Indonesia KCP Medan Marelan Raya.